Awareness, Attitudes, and Practices of the Exercise Buddy System Among Overweight and Obese Individuals in India: A Cross‐Sectional Study - Khyati Patel; Bhavana Gadhavi; Geeta Bhatt; Priti Mehendale (National Journal of Community Medicine)
Background: Overweight and obesity are growing health problems in India due to city living and lifestyle changes. Regular exercise helps prevent chronic diseases, but many people struggle to stick with it. The exercise buddy system, where two people exercise together, may improve motivation and consistency. However, few studies explore how well-known this method is. This study examined awareness, opinions, and use of the buddy system among overweight and obese adults in India.